ANGPTL4 May Regulate the Crosstalk Between Intervertebral Disc Degeneration and Type 2 Diabetes Mellitus: A Combined Analysis of Bioinformatics and Rat Models - Chen Y; Du H; Wang X; Li B; Chen X; Yang X; Zhao C; Zhao J (Dove Medical Press, 2023)
Yan Chen,1,* Han Du,1,* Xin Wang,1,* Baixing Li,1 Xuzhuo Chen,2 Xiao Yang,1 Changqing Zhao,1 Jie Zhao1 1Shanghai Key Laboratory of Orthopaedic Implants, Department of Orthopaedic Surgery, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of China; 2Department of Oral Surgery, Shanghai Key Laboratory of Stomatology & Shanghai Research Institute of Stomatology, National Clinical Research Center for Oral Diseases, Shanghai Ninth People's Hospital, College of Stomatology, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of China*These authors contributed equally to this workCorrespondence: Changqing Zhao; Xiao Yang, Shanghai Key Laboratory of Orthopaedic Implants, Department of Orthopaedic Surgery, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of China, Email zhaocq9hospital@163.com; walkingweapon@outlook.comIntroduction: The crosstalk between intervertebral disc degeneration (IVDD) and type 2 diabetes mellitus (T2DM) has been investigated. However, the common mechanism underlying this phenomenon has not been clearly elucidated. This study aimed to explore the shared gene signatures of IVDD and T2DM.Methods: The expression profiles of IVDD (GSE27494) and T2DM (GSE20966) were acquired from the Gene Expression Omnibus database. Five hub genes including ANGPTL4, CCL2, CCN3, THBS2, and INHBA were preliminarily screened. GO (Gene Ontology) enrichment analysis, functional correlation analysis, immune filtration, Transcription factors (TFs)-mRNA-miRNA coregulatory network, and potential drugs prediction were performed following the identification of hub genes. RNA sequencing, in vivo and in vitro experiments on rats were further performed to validate the expression and function of the target gene.Results: Five hub genes (ANGPTL4, CCL2, CCN3, THBS2, and INHBA) were identified. GO analysis demonstrated the regulation of the immune system, extracellular matrix (ECM), and SMAD protein signal transduction. There was a strong correlation between hub genes and different functions, including lipid metabolism, mitochondrial function, and ECM degradation. The immune filtration pattern grouped by disease and the expression of hub genes showed significant changes in the immune cell composition. TFs-mRNA-miRNA co-expression networks were constructed. In addition, pepstatin showed great drug-targeting relevance based on potential drugs prediction of hub genes. ANGPTL4, a gene that mediates the inhibition of lipoprotein lipase activity, was eventually determined after hub gene screening, validation by different datasets, RNA sequencing, and experiments.Discussion: This study screened five hub genes and ANGPTL4 was eventually determined as a potential target for the regulation of the crosstalk in patients with IVDD and T2DM.Keywords: ANGPTL4, biomarker, functional analysis, intervertebral disc degeneration, type 2 diabetes mellitus